2006
DOI: 10.1128/jvi.02700-05
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Vav by the Gammaherpesvirus M2 Protein Contributes to the Establishment of Viral Latency in B Lymphocytes

Abstract: Gammaherpesviruses subvert eukaryotic signaling pathways to favor latent infections in their cellular reservoirs. To this end, they express proteins that regulate or replace functionally specific signaling proteins of eukaryotic cells. Here we describe a new type of such viral-host interaction that is established through M2, a protein encoded by murine gammaherpesvirus 68. M2 associates with Vav proteins, a family of phosphorylation-dependent Rho/Rac exchange factors that play critical roles in lymphocyte sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
88
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(96 citation statements)
references
References 43 publications
7
88
0
1
Order By: Relevance
“…40,50). Finally, we detected induction of genes for M6 and M9, unique MHV68 genes whose functions are unknown.…”
mentioning
confidence: 93%
“…40,50). Finally, we detected induction of genes for M6 and M9, unique MHV68 genes whose functions are unknown.…”
mentioning
confidence: 93%
“…In vivo studies showed that the interaction of M2 with Vav proteins is important for the establishment of a latent infection of MHV-68 in B cells. 109,110 Retroviruses like HIV also may establish latency. In a transcriptome study in cell lines latently infected with HIV, Cdc42 expression was found to be downregulated, which perhaps may be involved in cellular maintenance of latency.…”
Section: Gene Expression and Latencymentioning
confidence: 99%
“…35,36 Depending on the endocytic uptake routes engaged during the initial interaction of the herpesviruses with the host, specific Rho GTPase signaling is triggered and significant actin cytoskeleton rearrangements are induced, [37][38][39][40] creating an optimal microenvironment for viral replication, persistence and dissemination. It is of interest that apart from lytic infection, the interactions between gamma-herpeviruses and Rho GTPase signaling remain active even during non-productive infection, facilitating either the establishment of latency 41 or affecting cell motility and invasion and promoting the oncogenic properties of these viruses. 36,42 Less information is available for b-herpesviruses.…”
Section: Introductionmentioning
confidence: 99%